The TARGET model and possibilities of its transposition to music education (Orfeu, 2025)
The TARGET model is a pedagogical intervention model that proposes the management, by the teacher, of six dimensions (task, authority, recognition, grouping, evaluation and time) that influence the educational structure of the classroom and the motivation to learn of students. Taking this model as a basis, the aims of this study were to investigate the application of the TARGET model in education and to propose ways to transpose it more specifically to music education. The methodology used for this purpose was a systematic literature review, carried out on the CAPES Periodical Portal, ProQuest and Web of Science platforms, which resulted in the identification and analysis of 12 articles. As a result of this research, possible applications of the six dimensions of the TARGET model in music education were explored, so that future research can verify in practice the viability and the effects of the presented proposals.
Keywords: TARGET model; music education; achievement goals; motivation